Numerical study on flow field and pollutant dispersion in an ideal street canyon within a real tree model at different wind velocities. (1st January 2021) - Wang, Le; Su, Junwei; Gu, Zhaolin; Tang, Liyu
Abstract: Studying the effects of trees on airflow and pollutant dispersion in urban street canyons is of considerable significance to clarify the laws of urban micro-scale airflow and pollutant dispersion. To characterize the trees in street canyons, different from the traditional vegetation resistance source method, in this paper, a fine tree model is used for numerical simulations of the airflow and pollutant dispersion in street canyons at varying inflow wind velocities. It is found during the study that the presence of trees physically blocks the airflow in street canyons. The airflow is sheared by the trunk, canopy, or branches, and then circumvents them, especially at a high inflow wind velocity. The low-velocity area in the street canyon distributes to the leeward side of the tree trunk as well as in the canopy area, and a discrete low-velocity distribution exists mainly in the canopy area. The average wind velocity in a street canyon with trees is approximately 39.5% lower at an inflow wind velocity of 1.7 m/s than that in a canyon without trees. In the presence of trees, the pollutant concentration in street canyons increases significantly, and the pollutants significantly accumulate between the tree trunk and the leeward side. With increasing inflow velocity, the pollutant concentration in a street canyon constantly changes but is much higher than that in the absence of trees. At a wind velocity of 5.7 m/s, the average pollutant concentration is 18.6% higher in street canyons with trees than in those without trees.